Effects of Hesperidin on Cisplatin-Induced Haematological and Biochemical Alterations in Rats - Sorathiya, Vishal L; Vihol, Priti D; Patel, Jignesh M; Patel, Jatin H; Khorajiya, Jaynudin H; Patel, Kishan M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Cisplatin, known as “penicillin of cancer” is an inorganic compound that is considered one of the best and first metal-based  chemotherapeutic drugs. Hesperidin is one of the major dietary flavanones that is found abundantly in many citrus fruits. The present  study was aimed to evaluate the ameliorative effects of hesperidin (@100 & 200 mg/kg b. wt.) in cisplatin (@ 7.5 mg/kg b.wt.) induced  haemato-biochemical alteration in rats (n=32) over a period of 14 days. There was a decrease in mean values of haemoglobin, packed  cell volume, platelets, total erythrocyte count and total leukocyte count in Group II (cisplatin, 7.5 mg/kg) and III (cisplatin plus 100 mg/ kg hesperidin) in comparison with Group I (control, 0.5 mL of carboxy methyl cellulose) and IV (cisplatin plus 200 mg/kg hesperidin)  at 14th day of experiment. Similarly, a significant elevation in serum AST, ALT, cholesterol, urea, creatinine and triglyceride values as  well as significant decrease in total protein and albumin values were noted in cisplatin treated rats (Group II) at 14th day of experiment.
Keywords: Cisplatin,; Haemato-biochemical; alterations; Hesperidin; Rats.